Coronal Plane Gap Increases Postoperative Pseudoarthrosis after Lateral Interbody Fusion for Adult Spinal Deformity - Eijiro Okada; Mitsuru Yagi; Yusuke Yamamoto; Satoshi Suzuki; Satoshi Nori; Osahiko Tsuji; Narihito Nagoshi; Nobuyuki Fujita; Masaya Nakamura; Morio Matsumoto; Kota Watanabe (Asian Spine Journal, 2022)
Study Design This is a retrospective study. Purpose This study aims to evaluate the risk factor associated with pseudoarthrosis after placement of lateral interbody fusion (LIF) cages for adult spinal deformity (ASD) treatment. Overview of Literature LIF technique is widely used for ASD correction. Furthermore, pseudoarthrosis is a major complication of fusion surgery required for revision surgery. Methods This study included 42 patients with ASD (two men and 40 women; 112 segments; mean, 68.5±8.4 years; and mean follow-up, 31.6±17.0 months) who underwent LIF and posterior correction surgery. The concave slot of the LIF cage was filled with an autologous iliac crest bone graft (IBG), and the convex slot with a porous hydroxyapatite/collagen (HAp/Col) composite was soaked with bone marrow aspirate. Endplate injury, the gap between vertebral endplate and cage in the coronal or sagittal plane, and fusion status were evaluated using computed tomography multiplanar reconstruction at 12 months after surgery. Moreover, the associated risk factors for pseudoarthrosis were analyzed. Results Fusion at LIF segments were observed in 71.4% segments at 12 months after surgery. Fusion on the concave slot (autologous IBG side), convex slot (porous HAp/Col composite side), and both concave and convex slots were observed in 66.1%, 37.5%, and 36.6% of patients, respectively. Moreover, pseudoarthrosis was observed in 28.6% at 12 months after surgery. Consequently, logistic regression analysis of the fusion at the LIF segment revealed that the gap between the LIF cage and endplate in the coronal plane (p=0.030; odds ratio, 0.183; 95% confidence interval, 0.030–0.183) was significantly associated with pseudoarthrosis at the LIF segments. Conclusions ASD surgery fusion rate using LIF cages was 71.4% at 12 months after surgery. The fusion rate was higher on the concave slot filled with autologous IBG than on the convex slot filled with a porous HAp/Col composite. The gap in the coronal plane was a risk factor for pseudoarthrosis at the LIF segment.